Grazing Pressure and Plant Functional Types in Puna Highlands, Northwestern Argentina - Quiroga Mendiola, Mariana; Tálamo, Andrés (Elsevier, 2024)
The Puna grasslands support grazing systems that produce meat and wool in multi-species herds, especially from llama (Lama glama) and sheep. However, it is yet unknown whether grazing pressure can modify grassland structure and Plant Functional Types diversity and cover in Puna grasslands. We analyzed the relationship between grazing pressure and Plant Functional Types by comparing transects located near stockyards (high grazing pressure) and far from them (low pressure) and by evaluating the relationship between the Plant Functional Types cover to a Grazing Pressure Index (GPI). This index incorporates the heterogeneity of traditional pastoral management. At two ecological sites (Ciénego and Tolar), we sampled paired transects (near-far). Plots near and far from corrals were similar in all the variables measured except for plots in Tolar, which tend to have higher total cover, possibly due to fecal fertilization near stockyards. Furthermore, we recorded an increase in total cover and grass cover at higher GPI in Ciénego, while in Tolar we found lower values of total cover and herbaceous dicotyledonous cover at intermediate intensities of GPI. The only negative relationship found was the cover of clonal and non-clonal shrubs, possibly explained by the greater use of these shrubs as firewood near stockyards. In summary, our study does not show important changes in Plant Functional Types as a function of grazing pressure in the studied grasslands probably because grazing pressure is diluted or diminished when livestock rotates in different areas and grazing durations vary. Finally, the long grazing history with which the Puna has evolved could also contribute to the co-structuration between native vegetation and livestock farming.